The analysis of technical design of special effects in musical theatre performances at Istana Budaya - Hashim, Hafshizan; Abd Rahman, Khairul Aidil Azlin; Zulkepeli, Mohd Kamil (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The aim of this paper is to examine the materials and techniques of technical production of special effects used in musical theatre performances at Istana Budaya. Musical theatre is a type of theatre that showcases various elements ofawe in its performances. Local productions are non-exceptional in this and most of them are now performing in Panggung Sari, Istana Budaya, Kuala Lumpur, Malaysia. Feed backs towards musical theatres at Istana Budaya have becoming more extravagant as each performance portrays lots of magical elements and more technical special effects (the designs of technical special effect thatare mesmerizing). Research on technical designs (building structures and creation of technical special effect) and technical effects are done in intention to comprehend and analyze the technicalities of special effects such as building materials, techniques, energy sources, method of implementation and the impacts of it in musical theatre productions particularly in Istana Budaya. There are three selected materials used in this research, and they are “Aladdin the Musical” (2007), “Puteri Gunung Ledang the Musical” (2006) and “Cats the Musical” (2002). The artworks are selected based on certain staging elements of musical theatres such as its ability to be sophisticated, the use of technology and the strong theatre building. In contrast, in Malaysia, only simple or basic equipment and techniques are utilized to enhance the magical elements in musical theatre performance which is by using special effects and technical design. The research findings are based on qualitative studies undertaken at Istana Budaya in the year of 2014-2016, among directors, designers, and artistic team, by using semi-structured interview. The interview consists of responsive materials from performances observation as well as analysis of the design materials or artifacts such as drawings, photos and viewing the recorded video. This paper is discussing the technical designs in musical theatre performances that are helpful in providing beneficial guidelines and solutions on the technical impacts of special effects in context of Malaysian theatre performances.